CVIc: A web platform for automated Coastal Vulnerability Index-based assessment - Liaskos, Alexandros; Petropoulos, George P.; Niki Evelpidou; Detsikas, Spyridon E. (Environmental Modelling & Software, 2025)
Intensifying climate change impacts, such as Sea-Level Rise (SLR), floods, extreme weather events and coastal erosion, threaten ecosystems, infrastructure, and human communities at a global scale, making vulnerability assessments a crucial prerequisite for identifying areas necessitating urgent and effective actions. The Coastal Vulnerability Index (CVI) is a widely used index-based methodology for such assessments; yet its implementation often relies on complex, manual workflows across multiple proprietary desktop Geographic Information Systems (GIS) software. Existing approaches limit accessibility, lack transparency, hinder reproducibility, and are frequently time-consuming. To address these challenges, CVIc (Coastal Vulnerability Index Compiler) is presented herein as a novel, open-source, and open-access geoprocessing web application for the computation of the CVI. CVIc provides an end-to-end dynamic workflow, guiding users from shoreline data import to the application of various standardized indices (CVI, ICVI). CVIc is deployed as a website (https://alexandrosliaskos.github.io/CVIc/) and features interactive tools for shoreline digitization, segmentation, parameter value assignment, and visualization and export of results. The only input requirements are a shoreline Shapefile input or a GeoTIFF image for digitization, and the knowledge of the spatial distribution of the parameter values for the area under study. By leveraging IndexedDB for browser-based data storage, CVIc operates without server-side dependencies, ensuring data privacy, protection and large-scale dataset processing. To our knowledge, this consists the first web solution of its kind, as its streamlined approach into a unified and user-friendly platform makes this type of analysis more feasible to researchers and coastal practitioners, while providing policymakers with more accessible and robust data for decision-making. Its open-source nature enables community-driven advancements, and the simple User Interface (UI) and map components mark it as appropriate for educational purposes.
Keywords: Automation; Coastal vulnerability index; EO-PERSIST; Geospatial software; Web application